On the Problem of Interlingual Homonyms in Slavic Languages (Using the Material of Slovak, Czech and Russian Languages) (Филологический класс, 2015)
The article considers the questions of formal similarities or equality and semantic differences on lexical level of the compared languages: Slovak, Czech and Russian ones. The phenomenon of interlingual homonyms is investigated in the article; special attention is given to terminological versions and the distinction between the concepts "homonymy" and "paronymy". The subject of investigation is the comparative analysis of the translations of literary texts from Russian into Slovak and from Czech into Slovak to identify the instances of negative interference in translation interlingual homonyms. On the base of the obtained results, the following conclusion is made: the so-called false friends are the stumbling block not only for the students of foreign language but for the professional interpreters, lexicographers and the specialists in machine translation. The results of the investigation can be applied in the process of teaching Slavic languages. The presented illustrative material confirms the necessity to continue research in this field and to apply the results in the training of linguists, including translators and lexicographers. The obtained results may become analogous for other research in the field of Slavic studies.